Sistem Pendukung Keputusan Seleksi Karyawan Baru Dengan Metode Saw - Ira afrilian Septiana; Eka Sefriyanto; Suyitno Adi Purnomo (Jurnal Cendikia, 2025)
In this era of globalization, companies are required to have quality human resources to compete in the international market. An effective and efficient employee selection process has become one of the important factors in obtaining employees that meet the company's needs. This research aims to develop a decision support system (DSS) that can assist companies in the process of selecting new employees using the Simple Additive Weighting (SAW) method. The SAW method is chosen because of its good capability in solving multi-criteria problems by converting various alternative criteria into a numerical scale, allowing for simple and comprehensive calculations. This system is built using a specific programming language and has been tested to ensure its accuracy and reliability. The results of this study indicate that the developed decision support system is capable of providing accurate and effective recommendations in the process of selecting new employees. This system is expected to become an important tool for companies in making timely and appropriate decisions, and can be adapted for various selection needs in the future.